(untitled) (Research, Society and Development, 2019)
Students are familiar and have easy access to smartphones, tablets, computers and applications and enjoy using them. Thus, the purpose of this article is to present a lesson proposal that uses digital technologies and its resources for the teaching-learning process in the mathematics discipline. This is a bibliographical review article. Thus, from the review: we identify the challenges and potentialities of Digital Information and Communication Technologies - TDIC applied to Education; we pointed out the main difficulties in teaching-learning "second degree function graph" content and suggested a lesson plan for teaching this content in math classes using two resources: GeoGebra software and videos on YouTube. The literature and the potentialities and characteristics of the suggested resources demonstrate how the proposal can contribute to a better understanding of the content, for example, in the student’s visualization of the function graph. Thus, we consider that the proposal presented favors the teaching-learning process.